Streptobacillus sp. isolated from a cat with pneumonia. Issue 2 (June 2014) - Eisenberg, Tobias; Nesseler, Anne; Nicklas, Werner; Spamer, Viola; Seeger, Helga; Zschöck, Michael
Abstract : Introduction: Streptobacillus moniliformis causes rat‐bite fever, an underdiagnosed zoonosis occurring worldwide. A variety of animals including livestock and exotic mammals are known to be susceptible hosts for this species, but little information is available regarding infection in companion animals. Case presentation: Following the necropsy of a domestic cat, bacteria displaying substantial characteristics of Streptobacillus sp. were cultured from pneumonic lung tissue. Streptobacillus ‐like morphological features observed included strictly microaerophilic pleomorphic Gram‐negative rods with bulbar swellings that grew exclusively in the presence of serum. Significant shared biochemical properties included negative reactions for cytochrome oxidase, catalase, urease, nitrate reduction and indole production, as well as broad antimicrobial susceptibility. These characteristics are all indicative of Streptobacillus moniliformis . However, 16S rRNA gene sequencing revealed only 98 % sequence homology to type strain DSM 12112. A mass spectrometry analysis confirmed the affiliation of the domestic cat isolate described in this study with bacteria of the genus Streptobacillus, but matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry indicated that it differed from nine reference strains of Streptobacillus moniliformis isolated from various sources and host species. Conclusion: This is the first evidence for clinical disease caused by a streptobacillary infection in a domestic cat.